2018
DOI: 10.3390/rs10091450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Methods for Estimating Land Surface Temperature from Landsat 8-TIRS Sensor Data

Abstract: After Landsat 8 was launched in 2013, it was observed that for Thermal Infrared sensor (TIRS) bands, radiance from outside of an instrument’s field-of-view produced a non-uniform ghost signal across the focal plane that varied depending on the out-of-scene content (i.e., the stray light effect). A new stray light correction algorithm (SLCA) is currently operational and has been implemented into the United States Geological Survey (USGS) ground system since February 2017. The SLCA has also been applied to repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 24 publications
(50 reference statements)
5
51
1
7
Order By: Relevance
“…The measured positive temperature bias of satellite vs. in situ measurements is consistent with previous calibrations/validations of ASTER kinetic surface temperatures (Tonooka and Palluconi, 2005) and our own ASTER thermal validations at an iceberg-choked lake and on melting snow and glacier clean-ice fields (Ramachandran et al, 2014). Validations of Landsat 8 temperatures have involved radiometrically very different types of surfaces (urban buildings, asphalt and orchards for instance) but have also shown biases and RMSEs similar to those of ASTER (García-Santos et al, 2018) and have revealed algorithm-dependent and humidity-dependent biases. Li and Jiang (2018) found a negative bias of about −0.49 K between Landsat 8 temperatures (cooler) compared to MODIS MOD11, which is roughly consistent with the Landsat 8/ASTER bias since ASTER temperatures were partly calibrated using MODIS (Arai, 1996).…”
Section: Glacier Calving and Iceberg Productionsupporting
confidence: 86%
See 1 more Smart Citation
“…The measured positive temperature bias of satellite vs. in situ measurements is consistent with previous calibrations/validations of ASTER kinetic surface temperatures (Tonooka and Palluconi, 2005) and our own ASTER thermal validations at an iceberg-choked lake and on melting snow and glacier clean-ice fields (Ramachandran et al, 2014). Validations of Landsat 8 temperatures have involved radiometrically very different types of surfaces (urban buildings, asphalt and orchards for instance) but have also shown biases and RMSEs similar to those of ASTER (García-Santos et al, 2018) and have revealed algorithm-dependent and humidity-dependent biases. Li and Jiang (2018) found a negative bias of about −0.49 K between Landsat 8 temperatures (cooler) compared to MODIS MOD11, which is roughly consistent with the Landsat 8/ASTER bias since ASTER temperatures were partly calibrated using MODIS (Arai, 1996).…”
Section: Glacier Calving and Iceberg Productionsupporting
confidence: 86%
“…The warmest mean lake temperatures observed with ASTER and Landsat thermal imagery were 10.7 and 10.8 • C for Thulagi Lake on 29 September 2015 and 30 September 2016; 4.2 and 7.2 • C at Lower Barun Lake on 9 October 2004 and 30 September 2015 and 8.6 and 9.6 • C for Imja Lake on 9 October 2004. When interpreting Figure 4, we should recall the RMSE evaluated for Landsat 8 surface temperatures of + −1.6-2 K (García-Santos et al, 2018) and ASTER (about + −0.8 K, Ramachandran et al, 2014), and the temperature bias of + 0.8 K for ASTER (Ramachandran et al, 2014). Considering these errors, it may be seen that Thulagi Lake well exceeds the 4 • C density-maximum temperature of water, but for Lower Barun, it did not clearly ever exceed that temperature.…”
Section: Satellite Surface Temperature Measurementsmentioning
confidence: 99%
“…In this study, the radiative transfer equation was used for Landsat 8 TIRS-10/11 to retrieve LSTs for Shenzhen. The main processes were defined with reference to Garcia-Santos [50]. The retrieved mean LSTs of Shenzhen on 1 and 23 October 2017 are displayed in Figure 3.…”
Section: Land Surface Temperature (Lst) Retrievalmentioning
confidence: 99%
“…where P is housing rental prices or house prices, and 1 , 2 , …, are the factors that impact P. In Equation (1), f is the relationship between and P, where the linear model, semi-log model, and double-log model were in existing studies. The linear model was used [35,[49][50][51] in this study to evaluate the economic value of green spaces in Shenzhen.…”
Section: Evaluating Modelmentioning
confidence: 99%
“…After analyzing the relevant sources of errors, the author showed that the split window method could be adopted with an accuracy of 3 • C. Among numerous applications of LST retrieval calculations, its application is still followed in estimating water status in the field [21]. In this regard, many studies have been carried out for developing and improving the LST retrieval methods [22][23][24][25][26] to estimate evapotranspiration. Moreover, the RS has been utilized for estimating vegetation indices (VI), such as the normalized difference vegetation index (NDVI) [27].…”
Section: Introductionmentioning
confidence: 99%